RET rearrangements are actionable alterations in breast cancer. Issue 1 (December 2018) - Paratala, Bhavna; Chung, Jon; Williams, Casey; Yilmazel, Bahar; Petrosky, Whitney; Williams, Kirstin; Schrock, Alexa; Gay, Laurie; Lee, Ellen; Dolfi, Sonia; Pham, Kien; Lin, Stephanie; et al.
Abstract Fusions involving the oncogenic geneRET have been observed in thyroid and lung cancers. Here we reportRET gene alterations, including amplification, missense mutations, known fusions, novel fusions, and rearrangements in breast cancer. Their frequency, oncogenic potential, and actionability in breast cancer are described. Two out of eightRET fusions (NCOA4-RET and a novelRASGEF1A-RET fusion) andRET amplification were functionally characterized and shown to activate RET kinase and drive signaling through MAPK and PI3K pathways. These fusions andRET amplification can induce transformation of non-tumorigenic cells, support xenograft tumor formation, and render sensitivity to RET inhibition. An index case of metastatic breast cancer progressing on HER2-targeted therapy was found to have theNCOA4-RET fusion. Subsequent treatment with the RET inhibitor cabozantinib led to a rapid clinical and radiographic response.RET alterations, identified by genomic profiling, are promising therapeutic targets and are present in a subset of breast cancers. Fusions of the gene RET have been described in thyroid and lung cancers. Here, the AUs identify RET gene alterations, including known fusions, novel fusions, and rearrangements in breast cancer (BC) that are involved in the tumorigenic process and show the benefit of RET therapy in a recurrent BC patient carrying the NCOA4-RET fusion.